"It was surprisingly equivalent to the appointment I had in person": Advantages and disadvantages of synchronous telehealth for delivering primary care for autistic adults. (August 2022) - Harris, Lauren; Gilmore, Daniel; Hanks, Christopher; Coury, Daniel; Moffatt-Bruce, Susan; Garvin, Jennifer H; Hand, Brittany N
Autistic adults experience barriers to primary care, including distant/inaccessible clinics, sensory stressors, and communication barriers with providers. Synchronous telehealth visits, termed "virtual visits, " may be a way to minimize these barriers. We investigated the advantages and disadvantages of primary care virtual visits using a phenomenological approach. We interviewed autistic adults ( n = 7) and caregivers of autistic adults ( n = 12) from one primary care clinic. Using thematic analysis, we identified three advantages to virtual visits: (1) increased patient comfort from avoiding travel to the clinic, crowded waiting rooms, and other sensory stressors; (2) increased safety by avoiding physical contact with others who may be sick; and (3) similar or better patient–provider communication than in-person visits. Disadvantages included the following: (1) Internet instability and other technological issues, (2) the inability to receive hands-on care from the provider, and (3) reduced patient engagement due to environmental distractions. Virtual visits may minimize barriers to care for autistic adults by reducing travel time, exposure to sensory stressors, and barriers to communication with the provider. While we recognize that virtual visits may not be appropriate for all patients or in all situations, they may be a promising model of health care delivery for autistic adults. Lay abstract: Autistic adults face many barriers to receiving quality primary health care like clinics that are far away and sensory sensitivities. Real-time telehealth visits, called "virtual visits, " are live video chats between the patient and provider. Virtual visits may minimize barriers to care for autistic adults. We wanted to describe advantages and disadvantages of using virtual visits for delivering primary health care for autistic adults. We interviewed 7 autistic adults and 12 caregivers of autistic adults who receive primary care through one clinic. Autistic adults and caregivers said advantages to virtual visits were that (1) patients were more comfortable at home, (2) patients could get health care while avoiding physical contact with other people during the pandemic, and (3) virtual visits were similar to or better than in-person visits. The disadvantages included that (1) there could be technology problems like grainy video, (2) the doctor could not physically examine the patient (e.g. look in ears), and (3) patients sometimes participated less in the virtual visit than they would in person. Virtual visits may be beneficial for autistic adults by eliminating travel to the clinic and avoiding stressful sensory stimuli. We recognize that virtual visits may not work for all patients or in all situations. However, our study shows that primary care virtual visits may be beneficial for autistic adults during and beyond the pandemic.